Culturally Responsive Pedagogy in Primary Education: Leveraging Bima Local Wisdom to Foster Student Learning Independence - Feni Febrianti; Anisa Ainul Mardiah; May Yati; Badrun Islma; Siti Julaika (Winaya Inspirasi Nusantara Foundation, 2026)
The paradigm shift toward the Kurikulum Merdeka in Indonesia demands that primary school students develop strong learner autonomy, yet conventional teacher-centered instructions and generic textbooks often fail to engage young learners. This study aims to develop and evaluate an instructional learning module based on local Bima culture designed to enhance the learning independence of fourth-grade elementary school students. Utilizing a research and development framework guided by the five-stage ADDIE framework (Analysis, Design, Development, Implementation, and Evaluation), this study involved 76 fourth-grade students across four elementary schools in the Soromandi sub-district. Data were gathered through expert validation sheets, teacher and student response questionnaires, and a specialized learning independence scale, and subsequently analyzed using descriptive statistics and a paired t-test. The structural validation yielded a material feasibility score of 87% and a media design score of 95%, classifying the module as highly suitable for classroom deployment. User response questionnaires confirmed that the instructional media was exceptionally practical, accessible, and user-friendly for daily classroom activities. Crucially, the paired t-test revealed a highly significant increase in student learning independence following the modular intervention (t= 23.102, p <0.001, df= 39), demonstrating marked improvements in student motivation, classroom initiative, self-confidence, and personal accountability. These findings imply that embedding indigenous cultural artifacts and local wisdom into elementary curricula offers a scalable pedagogical mechanism to foster self-regulated learning habits while preserving unique regional heritage.